Gambaran Strategi Coping Stress Siswa Kelas XII Sman 42 Jakarta dalam Menghadapi Ujian Nasional - Suprayogi, Muhamad Nanang (Humaniora, 2011)
This study intended to know the description of stress coping strategies of 12th grade students of Jakarta 42 State Senior High School in facing National Exam. This study stems from the interest of researchers towards the number of cases of high school students who do not pass the National Exam. Researchers seek to impart knowledge to students on how to cope with their stress effectively and to the school and parents for providing the proper approach for students to face the National Exam. This study is a quantitative study using questionnaires as a measurement to know the description of stress coping strategies of Jakarta 42 State Senior High School students. Research instruments are compiled based on the theory developed by Lahey. In this research, obtained results that the class XII students of SMAN 42 Jakarta have a more predominant use of effective coping to cope with their stress in facing the National Exam. The most widely used strategy is removing stress and managing stress reaction